Strategy Analysis of Business Competition Development Badan Usaha Milik Desa (BUMDES) - Trihudiyatmanto, M. (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
BumDesa Tani Makmur Piyungan Magelang is one of the BUMDesa in Sawangan District, Magelang Regency. This research aims to formulate a strategy for the development of the BUMDesa Tani Makmur in Piyungan Magelang as well as to find out what factors hinder and support the development of the BUMDesa Tani Makmur Piyungan Magelang through SWOT analysis, by analyzing internal factors and external factors. This research was conducted using interview, observation and questionnaire methods. The results of this study indicate that the appropriate strategy is an aggressive strategy, namely a strategy that utilizes internal strengths to maximize external opportunities. Suggestions for BUMDesa to increase the number of customers, promotions must be more intensive. Increase and maintain maximum service. The products offered should have advantages. In determining the marketing strategy, the BUMDesa Tani Makmur Piyungan Magelang must take advantage of the strengths and opportunities it has and pay attention to the weaknesses and threats it faces.